Design of Automatic Doors Using Body Temperature Sensors - Tri Isra Janwardi (PT Inovasi Pratama Internasional, 2020)
In today's very rapid technological developments, many tools or products are produced that can help humans in every activity they carry out. The application of technology that can facilitate human activities, for example, such as automatic doors. Where everyone who approaches the door, the door will open automatically because the human body temperature is detected. This electronic device that detects body temperature uses the MLX90614 temperature sensor. This tool can work with a distance of about 2 cm. With automatic doors using a temperature sensor, this can be applied to every door of a room with high mobility such as hotel and mall lobby doors.